2019
DOI: 10.1111/jcmm.14754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TIM‐4 protects against cerebral ischaemia‐reperfusion injury

Abstract: TIM-4 plays an important role in ischaemia-reperfusion injury of liver and kidney; however, the effects of TIM-4 on cerebral ischaemia-reperfusion injury (IRI) are unknown. The purpose of the present study was to investigate the potential role of TIM-4 in experimental brain ischaemia-reperfusion injury. In this study, cerebral ischaemia reperfusion was induced by transient middle cerebral artery occlusion (MCAO) for 1 hour in C57/BL6 mice. The TIM-4 expression was detected in vivo or vitro by real-time quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Perioperational administration of anti‐TIM‐4 Ab has been shown to protect livers, as well as kidneys and brains, from IRI, ( 18,19,22,23 ) which indicates a proinflammatory, rather than homeostatic, role of TIM‐4 in these organs. Interestingly, when we tested the Ab in our model, we found that it could either protect or damage livers depending on the time of the Ab administration: Liver IRI and inflammatory response were reduced when anti‐TIM‐4 was injected perioperationally at 2 hours, but enhanced when injected pre‐emptively at 48 hours, before the onset of liver ischemia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perioperational administration of anti‐TIM‐4 Ab has been shown to protect livers, as well as kidneys and brains, from IRI, ( 18,19,22,23 ) which indicates a proinflammatory, rather than homeostatic, role of TIM‐4 in these organs. Interestingly, when we tested the Ab in our model, we found that it could either protect or damage livers depending on the time of the Ab administration: Liver IRI and inflammatory response were reduced when anti‐TIM‐4 was injected perioperationally at 2 hours, but enhanced when injected pre‐emptively at 48 hours, before the onset of liver ischemia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we addressed the question of whether TIM-4, as a macrophage efferocytosis coreceptor, plays an immune-regulatory role in the pathogenesis of liver IRI. Given that TIM-4 has been studied in several organ ischemia models (18,19,22,23) and anti-TIM-4 Abs were shown to inhibit tissue-inflammatory activation and protect from IR injury, (22,23) the question we clarified first was how the anti-TIM-4 Ab affected liver macrophages in vivo. We revealed the depleting nature of this Ab in mice and found that the repopulation kinetics of the KC niche determines the effect of anti-TIM-4 on liver IRI (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TIM-1-TIM-4 axis was suggested as a novel intervention target for IRI. Direct inhibition or induced depression of TIM-1 and TIM-4 protected against liver and cerebral IRI ( 25 29 ). Blocking the TIM-1-TIM-4 pathway by anti-TIM monoclonal antibody also diminished inflammation and improve apoptosis and survival in renal IRI ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…TIM-4 serves a different role in atherosclerosis (Table Ⅲ). At present, the main treatment of atherosclerosis is to reduce blood lipids, but in the face of the concurrence of lipid accumulation and inflammatory immunity, this method is not satisfactory in controlling disease progression or pathological state (117). Innate and adaptive immunity as well as apoptotic cell clearance serve a central role in the development of atherosclerosis and TIM-4 may affect this process.…”
Section: Role Of Tim-4 In Liver Ischemia-reperfusion Injury (Iri)mentioning
confidence: 99%